Škrlatni kukuj Cucujus cinnaberinus (Cucujidae: Coleoptera) na Goričkem in prvo pojavljanje vrste Pytho depressus (Pythidae: Coleoptera) v Sloveniji - Kapla, Andrej (Acta entomologica slovenica (Ljubljana), 2021)
In the spring of 2020, we conducted the first comprehensive systematic inventory of the saproxylic beetle species Cucujus cinnaberinus (Scopoli, 1763) in the Goričko area (NE Slovenia). We searched for the species in dead standing and lying trunks in the appropriate early decomposition phase. A total of 445 dead trees were examined at 31 locations, of which the species was detected in 20 trees (4.5%) and 13 locations (41.9%), respectively. At the time of the inventory, we also recorded the species Pythodepressus (Linnaeus, 1767), for the first time in Slovenia. In Goričko, C. cinnaberinus prefers european ash (Fraxinus excelsior), red pine (Pinus sylvestris), poplar (Populus), oak (Quercus) and black locust (Robiniapseudoacacia) as habitat trees. Not the position of the trunk, but its size was found important for the species. It seems that Cucujus cinnaberinus in Goričko, although not abundant, is widespread throughout the area and needs to be protected with correct measures.
Keywords: Coleoptera; Cucujidae; Cucujus cinnaberinus; dead wood; habitat protection; microhabitat; mikrohabitat; odmrla lesna masa; preference trees; preferenčna drevesa; Pythidae; saproksilni hrošči; saproxylic beetles; varovanje habitata; Žuželke